(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Vandhyatva (infertility) is failure to conceive or give birth or experiencing Garbha Strava or Garbha pata (repeated abortion). Disturbed lifestyle, usage of contraceptives, stress, genetic problems, alcohol consumption and smoking addiction increases such cases day by day. Nowadays fallopian tube blockage has become one of the burning issues of female infertility. According to Ayurveda, successful conception depends upon Ritu, Kshetra, Ambu and Beeja. Beejagrahana is unable due to tubal blockage (Sanga Srotodusti of Arthavavaha) leads to failure of conception. Panchakarma plays an important role in treating female infertility and Uttara Basti is one of the best (Panchkarma therapy for the infertility treatment in Ayurveda). It detoxifies the uterine cavity and fallopian tubes, which clear the Srothoavarodha. Uttarbasti along with internal medication helps in Vata Dosha saman and remove the Sanga srotodusti. A diagnosed case of infertility due to bilateral tubal blockage, visited our clinic for treatment of tubal blockage and consequent infertility. Here is the case presentation of successful treatment with Ayurveda medicines and Uttara basti.